Unlocking Employee Potential: The Role of Job Security and Satisfaction in Performance - Rahmat, Muhammad; Wisra, Mefri Yudi (Manunggal Halim Jaya, 2026)
This study examines how job security and job satisfaction influence the performance of university lecturers in Indonesia, aiming to identify key factors that enhance academic professionals' potential and improve educational quality. The research employs a quantitative approach with a descriptive design, collecting data from Indonesian lecturers through purposive sampling. Survey questionnaires were distributed nationwide, and the gathered data were analyzed using SmartPLS to measure the impact of job security and job satisfaction on various performance indicators. The findings reveal that job security significantly improves lecturer performance, while job satisfaction demonstrates a stronger positive correlation. Lecturers with stable employment conditions and high job satisfaction exhibited better teaching quality, higher research productivity, and more impactful community engagement. The study underscores the critical relationship between employment stability, professional fulfillment, and academic performance. Therefore, higher education institutions should prioritize policies that strengthen job security and workplace satisfaction to optimize lecturer performance and institutional excellence. However, the study has certain limitations. Although it includes multiple institutions across Indonesia, regional variations in education systems may affect the generalizability of the results. Additionally, reliance on self-reported performance data may introduce some measurement bias.